Comparison of Engine Simulation Software for Development of Control System. (20th August 2013) - Chan, KinYip; Ordys, Andrzej; Volkov, Konstantin; Duran, Olga
Abstract : Most commonly used commercial engine simulation packages generate detailed estimation of the combustion and gas flow parameters. These parameters are required for advanced research on fluid flow and heat transfer and development of geometries of engine components. However, engine control involves different operating parameters. Various sensors are installed into the engine, the combustion performance is recorded, and data is sent to engine control unit (ECU). ECU computes the new set of parameters to make fine adjustments to actuators providing better engine performance. Such techniques include variable valve timing, variable ignition timing, variable air to fuel ratio, and variable compression ratio. In the present study, two of the commercial packages, Ricardo Wave and Lotus Engine Simulation, have been tested on the capabilities for engine control purposes. These packages are compared with an in-house developed package and with reference results available from the literature. Different numerical experiments have been carried out from which it can be concluded that all packages predict similar profiles of pressure and temperature in the engine cylinder. Moreover, those are in reasonable agreement with the reference results while in-house developed package is possible to run simulations with changing speed for engine control purpose.